2018
DOI: 10.1055/s-0044-101454
|View full text |Cite
|
Sign up to set email alerts
|

A History of Concussion Does Not Lead to an Increase in Ocular Near Point of Convergence

Abstract: Ocular near point of convergence (NPC) has been shown to be sensitive to the effects of concussion and subconcussive impacts. To determine if NPC is also sensitive to a previous history of concussion, male contact-sport athletes either with (n=26) or without (n=16) a history of at least one previous concussion had their NPC assessed. The results showed that participants with a history of concussion displayed NPC values (9.4±1.6 cm) indistinguishable from those with no history of concussion (8.4±2.1 cm, t-test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Although NPC distance is infrequently investigated in the long term following concussion, one study demonstrated that student-athletes with a history of concussion (>6 months) exhibited similar NPC distance compared with a control group without a concussion history. 42 In addition, rates of receded NPC (>5 cm) in our concussion group approximated the proportion of athletes in other studies who exhibit receded NPC acutely and subacutely following concussion (36%-50%). 12,14,27,32,35 The rates of receded NPC (>5 cm) in the control group at the 6-month (30%) and 1-year (32%) study assessments fall within the range (11%-33%) of receded NPC (>5 cm) proportions observed across studies evaluating healthy, nonconcussed athletes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although NPC distance is infrequently investigated in the long term following concussion, one study demonstrated that student-athletes with a history of concussion (>6 months) exhibited similar NPC distance compared with a control group without a concussion history. 42 In addition, rates of receded NPC (>5 cm) in our concussion group approximated the proportion of athletes in other studies who exhibit receded NPC acutely and subacutely following concussion (36%-50%). 12,14,27,32,35 The rates of receded NPC (>5 cm) in the control group at the 6-month (30%) and 1-year (32%) study assessments fall within the range (11%-33%) of receded NPC (>5 cm) proportions observed across studies evaluating healthy, nonconcussed athletes.…”
Section: Discussionsupporting
confidence: 64%
“…These findings align with prior studies investigating NPC distance in concussed and control athletes following sport-related concussion. Although NPC distance is infrequently investigated in the long term following concussion, one study demonstrated that student-athletes with a history of concussion (>6 months) exhibited similar NPC distance compared with a control group without a concussion history 42. In addition, rates of receded NPC (>5 cm) in our concussion group approximated the proportion of athletes in other studies who exhibit receded NPC acutely and subacutely following concussion (36%-50%) 12,14,27,32,35.…”
Section: Discussionmentioning
confidence: 99%
“…A history of one or more prior concussions increases the odds 5.8 times of sustaining another concussion [34,36]. However, a history of concussion does not result in poorer performance on the NPC [58] or the K-D test [10] in isolation. Therefore, combining both visual assessment metrics while considering age in those with and without a history of concussion might better identify those who have sustained a concussion.…”
Section: Eye Scanning and Cognitive Functionmentioning
confidence: 99%
“…Pearce et al showed differences in NPC between concussed and non-concussed athletes (12.6 ± 9.0 vs. 1.5 ± 1.5) [48]. van Donkelaar et al identified that NPC did not adequately discriminate between those with and without a concussion history (9.4 ± 1.6 vs. 8.4 ± 2.1 cm) [58]. Del Rossi reported that about 20% of the NPC were below the cut-off of ≥5 cm, leading to incorrect categorization, while there was no association between NPC and a concussion history despite better NPC in those with a history of concussion [62].…”
Section: Contrasting Npc Research Findingsmentioning
confidence: 99%